Look legal and political consequences of media concentration for the development of the agenda and public policy - Domínguez Vera, Luis Fernando (2016)
This article applies the tools provided by political science and policy analysis to assess all the practical consequences of media concentration, taking as  reference  the  right to freedom of expression and jurisprudential development in the Inter-American Human Rights System (ISHR).